The parallel mediation effects of nutrition, physical activity on depression and sarcopenia risk among older people with diabetes - Miaomiao, Wang; Qiao, Liu; Xiaodi, Guo; Xiling, Hu; Li, Cheng (Frontiers in Public Health, 2025)
BackgroundDepression and sarcopenia pose significant health challenges for older adults with diabetes. While previous studies have established a positive association between depression and the risk of sarcopenia, the underlying mechanisms driving this relationship remain poorly understood.ObjectivesThe aim of this study was to investigate the relationship between depression and sarcopenia risk in older adults with diabetes, with a particular focus on the potential mediating roles of nutrition and physical activity. The findings would provide empirical evidence to inform future prevention and intervention strategies.DesignA multi-center cross-sectional study.MethodsA total of 312 older adult patients with diabetes were selected from two hospitals using a convenience sampling method. The study evaluated demographic and clinical characteristics, along with factors such as nutrition, physical activity, depression, and sarcopenia risk. A multivariate logistic regression model was used to assess the association between depression and sarcopenia risk. Furthermore, the bootstrap resampling method, involving 5,000 samples and a 95% confidence interval (CI), was employed to examine the parallel mediating effects and determine whether nutrition and physical activity mediated the relationship between depression and sarcopenia risk. Data analysis was conducted using SPSS 26.0 and Mplus 7.0 software.ResultsA total of 58.0% of participants were found to be at high risk for sarcopenia. Depression was shown to influence sarcopenia risk significantly, with nutrition and physical activity acting as parallel mediators. The total indirect effect was estimated at 0.087 (95% CI: 0.056, 0.126), accounting for 34.9% of the total effect (total effect = 0.249, 95% CI: 0.175, 0.311). Notably, nutrition played a crucial role in this mediation, contributing 61% of the total indirect effect.ConclusionA significant proportion of older adults with diabetes were found to be at high risk of sarcopenia, which underscores the importance of routine screening for sarcopenia risk in older adults with diabetes. Depression was strongly associated with sarcopenia risk, with nutrition and physical activity acting as parallel mediators in this relationship. Given the pivotal role of nutrition in this parallel mediation model, the implementation of individualized nutrition plans is crucial for preventing muscle loss and reducing the risk of sarcopenia.